Response of Chinese cabbage (Brassica rapa subsp. pekinensis) to bacterial soft rot infection by change of soil microbial community in root zone - Li, Xuqing; Ren, Xiaoxu; Ibrahim, Ezzeldin; Kong, Haimin; Wang, Maofeng; Xia, Jiaojiao; Wang, Hong; Shou, Linfei; Zhou, Tiefeng; Li, Bin; Yan, Jianli (Frontiers in Microbiology, 2024)
Chinese cabbage, scientifically known as Brassica rapa subsp. pekinensis, is a highly popular vegetable in China for its delectable taste. However, the occurrence of bacterial soft rot disease poses a significant threat to its growth and overall development. Consequently, this study aimed to explore the defense mechanisms employed by Chinese cabbage against bacterial soft rot disease. Specifically, the investigation focused on understanding the relationship between the disease and the microbial communities present in the soil surrounding the roots of Chinese cabbage. Significant disparities were observed in the composition of microbial communities present in the root-zone soil of healthy Chinese cabbage plants compared to those affected by Pectobacterium brasiliense-caused soft rot disease. The analysis of 16S rRNA gene high-throughput sequencing results revealed a lower abundance of Proteobacteria (8.39%), Acidobacteriot (0.85), Sphingomonas (3.51%), and Vicinamibacteraceae (1.48%), whereas Firmicutes (113.76%), Bacteroidota (8.71%), Chloroflexi (4.89%), Actinobacteriota (1.71%), A4b (15.52%), Vicinamibacterales (1.62%), and Gemmatimonadaceae (1.35%) were more prevalent in healthy plant soils. Similarly, the analysis of ITS gene high-throughput sequencing results indicated a reduced occurrence of Chytridiomycota (23.58%), Basidiomycota (21.80%), Plectosphaerella (86.22%), and Agaricomycetes (22.57%) in healthy soils. In comparison, Mortierellomycota (50.72%), Ascomycota (31.22%), Podospora (485.08%), and Mortierella (51.59%) were more abundant in healthy plant soils. In addition, a total of fifteen bacterial strains were isolated from the root-zone soil of diseased Chinese cabbage plants. These isolated strains demonstrated the ability to fix nitrogen (with the exception of ZT20, ZT26, ZT41, ZT45, and ZT61), produce siderophores and indole acetic acid (IAA), and solubilize phosphate. Notably, ZT14 (Citrobacter freundii), ZT33 (Enterobacter cloacae), ZT41 (Myroides odoratimimus), ZT52 (Bacillus paramycoides), ZT58 (Klebsiella pasteurii), ZT45 (Klebsiella aerogenes), and ZT32 (Pseudomonas putida) exhibited significant growth-promoting effects as determined by the plant growth promotion (PGP) tests. Consequently, this investigation not only confirmed the presence of the soft rot pathogen in Chinese cabbage plants in Hangzhou, China, but also advanced our understanding of the defense mechanisms employed by Chinese cabbage to combat soft rot-induced stress. Additionally, it identified promising plant-growth-promoting microbes (PGPMs) that could be utilized in the future to enhance the Chinese cabbage industry.